The island of lost girls : a novel - Marwood, Alex (Harper, an imprint of HarperCollinsPublishers, 2023)
Desperately searching for her seventeen-year-old daughter Gemma, Robin is led to La Kastellana, a place of sun-drenched glamor and obscene wealth, where someone is waiting for the right moment to expose the dark truth of what really happens on the island of lost girls.